The Transformation of Bali's Digital Nomad Ecosystem in the Wake of the Russian-Ukrainian War - Astuti, Ni Nyoman Sri; Virginiya, Putu Tika; Sanjiwani, I Gusti Agung Mirah; Bagiastuti, Ni Ketut (Politeknik Pariwisata Makassar, Indonesia, 2025)
This research analyzes the transformation of the digital nomad ecosystem in Bali as a result of the Russia-Ukraine conflict that began in February 2022. Using a qualitative approach with an exploratory case study design, this research reveals how the conflict has triggered a wave of Russian migration to Bali, which increased from around 1,800 people in the pre-pandemic period to more than 58,000 people in 2022. This phenomenon has created “Russian enclaves” especially in the Canggu and Uluwatu areas, triggering significant transformations in demographic, economic, regulatory and socio-cultural aspects. The results show a restructuring of the local economy, characterized by a 35-40% increase in property prices during 2022-2023, a proliferation of Russian-oriented businesses, and a shift in the local tourism value chain. Regulatory challenges are a crucial issue, especially regarding visa compliance and digital nomad work activities that fall in the regulatory “gray zone”. Socio-cultural dynamics show a complex spectrum of interactions, from social segregation to forms of cultural adaptation and acculturation. Local Balinese communities demonstrate significant adaptive capacity through the involvement of adat institutions in property regulation and cultural preservation initiatives. This research contributes to the theoretical discourse on “crisis-driven lifestyle migration” and “creative resilience” of local communities in response to global transformation. The implications of the research highlight the importance of integrated policies to manage the digital nomad phenomenon, ensure equitable distribution of economic benefits, and preserve local cultural values amidst the dynamics of global mobility.